ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN PENDAPATAN DI SULAWESI - Agiel Pangestu Wibowo (2023)
Sulawesi as one of the five largest islands in Indonesia has significant consequences for social and economic sustainability. The negative impact that arises from the high population in Indonesia is income inequality. The research objective is to analyze macroeconomic indicators that affect income inequality in Sulawesi which ranks third in terms of inequality in Indonesia by looking at a better understanding of regional economic dynamics in the region in 2010-2022. The objective of this study is to determine the influence of HDI (Human Development Index), minimum wage, and Gross Regional Domestic Product (GRDP) on income inequality in the provinces of Sulawesi Island. The data for this research were obtained from the Central Statistics Agency, and the analysis technique used was panel data regression with the Stata program, with a standard significance level of 5%. Based on the data analysis, the following findings were obtained: (1) HDI has a negative and significant effect on income inequality (2) minimum wage has no significant effect on income inequality (3) GRDP has a positive and significant effect on income inequality with all variables simultaneously influencing income inequality in Sulawesi.